Value Chain Production Association for Pink Pepper Bananas: Research in Yen Lac District, Vinh Phuc Province, Vietnam - Ly, Tran Nguyen; Linh, Pham Nguyen My; Long, Pham Thai; Hương, Nguyen Thi Thu; Nang, Đo Thi; Thuc, Đo Thi (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">In Vietnam, there are various types of bananas, some of them have become regional specialties of many regions such as: Pink Pepper banana, Western banana, King banana, old banana, etc. Nowadays, Pink Pepper banana is the most popular grown banana with high potential for domestic and international markets. In order to contribute to adding value to agricultural products, linking production along the value chain for Pink Pepper bananas is an urgent issue for policy makers as well as businesses and farmers. This article focuses on analyzing the current status of value chain production linkage for this specific type of bananas in Yen Lac District, Vinh Phuc Province, Vietnam, at the same time, showing results, limitations, causes and recommendations to promote production linkages in the value chain for Vietnamese Pink Pepper banana products in the context of world economic integration.